2020
DOI: 10.1021/acsami.0c06783
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Impact of Heat Generation Using Nanographene-Based Light-Emitting Electrochemical Cells

Abstract: Self-heating in light-emitting electrochemical cells (LECs) has been long overlooked, while it has a significant impact on i) device chromaticity by changing the electroluminescent band shape, ii) device efficiency due to thermal quenching and exciton dissociation reducing the external quantum efficiency (EQE), and iii) device stability due to thermal quenching of excitons and formation of doped species, phase separation, and collapse of the intrinsic emitting zone. Herein, we reveal, for the first time, a dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Thus, our conclusion is that both the OLED and LEC devices exhibit similar qualitative behavior with a steady‐state exciton distribution that is migrating from closer to the anode at room temperature toward the center of the interelectrode gap at elevated temperatures. At this point, we wish to mention that other temperature‐induced effects, such as a changing effective width of the exciton distribution or a shifting exciton environment, [ 12,26 ] also can influence the device performance, but that an investigation on these effects are outside the scope of this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our conclusion is that both the OLED and LEC devices exhibit similar qualitative behavior with a steady‐state exciton distribution that is migrating from closer to the anode at room temperature toward the center of the interelectrode gap at elevated temperatures. At this point, we wish to mention that other temperature‐induced effects, such as a changing effective width of the exciton distribution or a shifting exciton environment, [ 12,26 ] also can influence the device performance, but that an investigation on these effects are outside the scope of this study.…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 ] In this context, we mention that Gao and coworkers utilized a temperature‐activated electrolyte phase transition for the attainment of LEC devices with very fast turn‐on time, [ 11a,11b ] and that recent studies established the strong effects that self‐heating can have on the operation of free‐standing LEC devices. [ 11c,12 ] However, we also note that a systematic study aimed at establishing the influence of temperature on LEC operation is lacking. Moreover, a direct comparison between the effects of temperature on OLED and LEC devices based on the same OSC is, to the best of our understanding, nonexistent in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…The so-fabricated LECs were measured with the coupled Avantes spectrophotometers Avaspec-ULS2048L-USB2 and AvaSpec-ULS2048CL-EVO for high UV-Vis and NIR sensitivity, respectively, and a calibrated integrated sphere Avasphere 30-Irrad and a Botest OLT OLED Lifetime-Test System, as described in previous contributions. [13,53] EIS assays were conducted with a potentiostat/galvanostat PGSTAT204 (Metrohm μAutolabIII) with EIS frequency response analyser module (FRA2). The applied voltage ranged from 0 to 4 V. The obtained data were fitted with the Nova software 1.1 using the circuit model shown in Figure S63, Supporting Information, as described in previous contributions.…”
Section: Methodsmentioning
confidence: 99%
“…The solution was clear and brownyellow and, after the release of the pressure inside the reactor vial, a yellow precipitate formed spontaneously. The needle-shaped crystallites were washed several times with a petroleum ether:ethyl ether 3:1 mixture (yield: 48%, 53 7.66 (tt, J = 6.9, 0.9 Hz, 2H), 7.62-7.57 (m, 1H), 7.42 (ddd, J = 9.2, 6.5, 1.0 Hz, 1H), 7.14 (ddd, J = 7.2, 6.5, 1.2 Hz, 1H), 5.26 (q, J = 7.2 Hz, 2H), 1.77 (t, J = 7.2 Hz, 3H); 13 [1,5-…”
Section: Synthesismentioning
confidence: 99%
“…One of the methods to disrupt aggregates in both the ground and excited states involves the employment of a polymeric matrix. We selected PMMA and PS as polymeric matrices, since they are the most widely used in literature for thin film preparation [52,53]. The results obtained demonstrated that the aggregation behavior was reduced with both matrices.…”
Section: Notes About the Photophysical Propertiesmentioning
confidence: 99%